Unique Pattern of Intrahepatic T-cell Clonality in Biliary Atresia Livers Versus Intestinal Controls: A Pilot Study. Issue 2 (24th May 2021) - Ogholikhan, Sina; Schwarz, Kathleen B.; Anders, Robert
Abstract : Supplemental Digital Content is available in the text. Abstract : Biliary atresia (BA) is a rare infantile cholangiopathy of unclear etiology proposed by some to be due to virus-induced autoreactive T-cell-mediated inflammation. The hallmark of T cell activity is clonal expansion of T lymphocytes expressing similar T-cell receptor (TCR) variable regions of the β-chain. Objective: To test our hypothesis that BA liver tissues would show clonal expansion of 1 or several TCRs. Methods: The complementarity-determining region 3 region of the β-chain of the TCR was characterized using next-generation sequencing of 7 BA liver samples (age 51 ± 14 days) and 9 intestinal control samples (age 38 ± 16 days). Following sequencing, clonality scores, various VDJ recombinations, total and productive templates, and complementarity-determining region 3 length were measured using the immunoSEQ Analyzer. Results: Next-generation sequencing revealed 1 common TCR rearrangement in 3 BA samples not found in controls. There was a highly diverse TCR population among BA liver and the control samples. The clonality scores ranged from 0.0004 to 0.0062 using a Shannon's entropy score, with numbers close to 0 being highly diverse and numbers close to 1 being highly clonal. The most common TCR VDJ recombinations comprised 1.47–12.9% of the total population of TCR for the BA tissues and 1.05–10.3% for the control samples. Conclusions: Our results show a highly diverse TCR repertoire among all of our samples. However, predominant TCR clonality was not found in any sample. Further studies are required for any possible antigenic triggers responsible for the unique T-cell rearrangements observed in the BA samples.